(untitled) (Indian Journal of Animal Production and Management, 2015)
objective to work out the net returns from milk production of different breeds. Altogether 200 farmers were selected for the present study. Out of this, 142, 31, 24 and 3 farmers were rearing local cattle calving annually (Group-I), local cattle calving alternate year (Group-II), cross bred cattle (Group-III) and both breeds (Group-IV) were selected respectively by stratified random sampling technique. The average daily milk yield per milch cow per day was 0.34, 0.30, 9.48 and 3.34 litres group I, II, III and IV respectively. The average net returns were negative for both non-descript local cattle breeds (-Rs. 0.13 and -Rs. 4.48), and highest for crossbred with Rs. 247.41 per milch cow per day followed by the farmers having both breeds (Rs. 65.51)